In defense of populism : protest and American democracy - Critchlow, Donald T., 1948- (University of Pennsylvania Press, 2020)
"In Defense of Populism challenges didactic accounts of populism as either simply expressions of the oppressed demanding that the democratic dream be realized or anxiety-ridden, anti-intellectual, paranoid, anti-democratic reactions to a changing order. Instead, this book submits that grassroots activist movements-populist movements-are essential to American democracy. At decisive points in American politics, social protest movements-whether on the left or the right-force established parties and leaders to bow to reform. In this way, anti-elitist social protest becomes absorbed by established powers. At the same time, the demands for democratic reform become institutionalized in the modern American state, ironically creating an enlarged bureaucratic government that is further removed from the people. This progression from protest to political absorption to institutionalization is evidenced in critical episodes in the American reform tradition. Indeed, American history is replete with these cycles of political disequilibrium followed by stabilization. In arguing for the necessary importance of populism to political reform, this book explores specific episodes in modern American history that reveal the interplay of populist social action and party reform: agrarian populism in the late nineteenth century, anti-corporatism in the Progressive Era, class protest during the New Deal, the struggle for black equality in the early Cold War era, second-wave feminism in the 1970s, and anti-statist New Right protest in the late twentieth century."--